Glossing for Improved Comprehension Progress and Prospect - Otto, Wayne; Hayes, Bernie ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
The terms gloss and glossing are being used to designate and describe the systematic use of marginal notes and other extra-text notations to direct readers' attention while they read. Gloss notations may serve as an aid to direct students to content areas of text and to levels of understanding that make optimal use of their current--and sometimes limited--reading ability. Since one purpose for using gloss is to encourage development and application of specific comprehension skills and the "general strategies" that efficient readers use in understanding text, it seems appropriate to use reading materials that are designed to teach reading skills and strategies. Three possible times to introduce gloss activities include (1) the initial stages of reading instruction, (2) the transition from learning reading skills in a reading class to applying them to content area materials, and (3) during remedial instruction. It must be noted that too much gloss may interfere with students' understanding, while too little gloss is likely to have no effect at all on their understanding. Also, the stages of gloss may be primarily reader/text dependent. Ultimately, glossing is both a way to strengthen students' reading comprehension skills and strategies, and a means to provide students with the metacognitive knowledge and insights assumed to underlie the ability to control one's own mental activities. (HOD)
ERIC Note: Paper presented at the Annual Meeting of the American Reading Forum (2nd, Sarasota, FL, December 10-12, 1981).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Content Area Reading; Elementary Secondary Education; Reading Comprehension; Reading Instruction; Reading Materials; Teaching Methods; Glossing -- Reading Strategies; Note Taking; Opinion Papers; Speeches/Meeting Papers